Sensing technologies for precision irrigation - Culibrk, Dubravko (SpringerBriefs in Electrical and Computer Engineering,, 2014)
This brief provides an overview of state-of-the-art sensing technologies relevant to the problem of precision irrigation, an emerging field within the domain of precision agriculture. Applications of wireless sensor networks, satellite data and geographic information systems in the domain are covered. This brief presents the basic concepts of the technologies and emphasizes the practical aspects that enable the implementation of intelligent irrigation systems. The authors target a broad audience interested in this theme and organize the content in five chapters, each concerned with a specific technology needed to address the problem of optimal crop irrigation. Professionals and researchers will find the text a thorough survey with practical applications.